Landslide hazard assessment in the Three Gorges area of the Yangtze river using ASTER imagery: Zigui-Badong (2004)
This paper reports a regional assessment of landslide hazard in the Three Gorges area, China, based on Terra-1 satellite Advanced Spaceborne Thermal Emission Radiometer (ASTER) imagery data, including a stereo image-derived Digital Elevation Model (DEM) and multi-spectral reflective and thermal imagery, in combination with limited field investigation. The Three Gorges dam and reservoir project has gained international attention, not only for its great potential for hydro-electrical power generation and flood control, but also for its potentially harmful effects on the environment and socio-economy. The most significant and widespread natural hazard in the region is slope instability. A simple, multi-variable elimination and characterisation model, employing geometric mean and Boolean decision rules, has been applied to a multi-criterion image dataset to categorise the area into a series of potential landslide hazard levels, which are presented in map form. The results presented here show high levels of hazard in and around all the main inhabited areas along the river. Limited fieldwork has been conducted to provide reliable ground control and the results of this paper show good correlation with this field evidence.